Band of brothers : E Company, 506th Regiment, 101st Airborne from Normandy to Hitler's Eagle's Nest - Ambrose, Stephen E. (New York : Simon & Schuster, 2001)
A look at the exploits of the men of E Company during World War II describes how they parachuted into France early D-Day morning, parachuted into Holland during the Arnhem campaign, and captured Hitler's Bavarian outpost.
"We wanted those wings"; Camp Toccoa, July-December 1942 -- "Stand up and hook up"; Benning, Mackall, Bragg, Shanks, December 1942-September 1943 -- "Duties of the latrine orderly"; Aldbourne, September 1943-March 1944 -- "Look out, Hitler! Here we come!"; Slapton Sands, Uppottery, April 1-June 5, 1944 -- "Follow me"; Normandy, June 6, 1944 -- "Move out!"; Carentan, June 7-July 12, 1944 -- Healing wounds and scrubbed missions; Aldbourne, July 13-September 16, 1944 -- "Hell's highway"; Holland, September 17-October 1, 1944 -- Island; Holland, October 2-November 25, 1944 -- Resting, recovering, and refitting: Mourmelon-le-Grand, November 26-December 18, 1944 -- "They got us surrounded-the poor bastards"; Bastogne, December 19-31, 1944 -- Breaking point; Bastogne, January 1-13, 1945 -- Attack; Noville, January 14-17, 1945 -- Patrol: Haguenau, January 18-February 23, 1945 -- "Best feeling in the world": Mourmelon, February 25-April 2, 1945 -- Getting to know the enemy: Germany, April 2-30, 1945 -- Drinking Hitler's champagne; Berchtesgaden, May 1-8, 1945 -- Soldier's dream life; Austria, May 8-July 31, 1945 -- Postwar careers; 1945-1991.
Includes bibliographical references and index.
Keywords: United States. -- Army. -- Parachute Infantry Regiment, 506th. -- Company E -- History; World War, 1939-1945 -- Regimental histories -- United States; World War, 1939-1945 -- Campaigns -- Western Front; USA -- Parachute Infantry Regiment (506); Weltkrieg (1939-1945); Geschichte 1944-1945